Determinan Of Muḍārabah Deposits At Sharia Commercial Banks In Indonesia - Nofinawati; Nasution, Adanan Murroh; Reski Amanah (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
As a financial institution, Islamic banking has a function as a collector of funds from the community. A fund-raising product in the form of deposits. Muḍārabah deposits are public investments whose withdrawals can only be made within a certain period of time according to the agreement. The largest fundraiser from deposits is deposit products compared to other products. The background of the problem in this study is based on the data obtained that the number of Muḍārabah deposits fluctuated in 2018-2023 as well as the Profit Sharing and Bi Rate which fluctuated in the Profit Sharing and Bi Rate.The purpose of this study is to determine the Effect of Profit Sharing and Bi Rate on Muḍārabah Deposits in Sharia Commercial Banks in Indonesia partially and simultaneously. The type of research is quantitative research with the data source used in the form of secondary data from the OJK's annual financial statements within the last 5 years. The data analysis method used is panel data with an analysis tool, namely panel data regression using the eviews 12 software application and Microsoft Excel. Using purpossive sampling techniques with a sample of 8 banks, the population in this study amounted to 13 Sharia Commercial Banks. The results of the study show that partially (t-test) the Profit Sharing variable has a significant effect on Muḍārabah Deposits. The Bi Rate variable does not have a significant effect on Muḍārabah Deposits. Meanwhile, simultaneously, the independent variables of Profit Sharing and Bi Rate have an effect on Muḍārabah Deposits in Sharia Commercial Banks in Indonesia.